A multicentred phase III comparative study between single-implant containing 3-ketodesogestrel (Implanon®) and implants containing levonorgestrel (Norplant®) II. Vaginal bleeding patterns (Faculty of Medicine Universitas Indonesia, 1999)
[no abstract available]